Customer Interaction on Social Media and Its Impact on the Brand Image of MSMEs: A Case Study of Me.lookal MSME in Bogor City - Febriantina Dewi; Retnaningsih; Adinda Kirana Murni Siregar (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Digital transformation has positioned social media as a strategic tool for small and medium enterprises (SMEs) to build customer relationships and strengthen brand image. This study investigates the influence of customer engagement, customer feedback, and SME responses on the brand image of Me.lookal. A quantitative approach was applied using a survey method with active customers of Me.lookal as respondents. Primary data were collected through online questionnaires, while secondary data were obtained from Me.lookal’s social media analytics. The data were analyzed using multiple linear regression. The findings reveal that customer engagement does not directly affect brand image, whereas customer feedback significantly influences it. Moreover, SME responses serve as a mediator between customer engagement and brand image, though not significantly mediating the relationship between customer feedback and brand image. These results suggest that Me.lookal’s brand strength lies in its capacity to respond effectively and promptly to customer interactions, as timely responses can convert engagement into a positive brand perception. Practical implications recommend improving responsiveness to feedback, enhancing engagement quality, and optimizing customer insights. Developing a holistic strategy that integrates engagement, feedback, and responses, along with continuous monitoring and evaluation, is essential to sustain and strengthen Me.lookal’s brand image.